Moral Disagreement in Anglican – Roman Catholic Relations - O'Donovan, Oliver (Ecclesiology, 2021)
Abstract The belief that the Anglican and Roman Catholic churches were divided by moral disagreements came to prominence in the early 1980s and affected the direction of ecumenical dialogue. But no moral disagreements go back to the Reformation era, and the perception of moral difference has undergone many changes since that time, especially reflecting differences of social and political setting. A moral agreement or disagreement is difficult to chart with precision. It is not embodied in a formulation of moral doctrine, since moral reason functions on two planes, that of evaluative description and that of deliberation and decision. Disagreement is phenomenologically present as offence, which has its own dynamic of expansion. Addressing offence, a task involving lay, theological and episcopal contributions, is the primary way in which moral agreement has to be sought and defended.